Efforts to Increase Public Awareness in Tonja Subdistrict Regarding Preventing Abstention Through the Smart Voting Movement - Ni Luh Putu Intan Rahayu Dewi; I Nengah Wirsa (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
In the implementation of democracy, a significant question arises regarding how the ideal concept of democracy is carried out Providing education about the importance of increasing awareness of voting rights in the 2024 elections aims to make people realize that abstaining from voting or not choosing is a mistake. The potential problems of the public about elections are fear of the wrong way to vote, limited knowledge and physical limitations. From the last 5 years, this is very taken for granted by the community because people assume that only those who have perfect knowledge and physique can voteIf this problem is not immediately addressed, more and more people in this Indonesian country will be lazy to come to the polling station and vote. This can also make the image of the nation less good. So with that, I held a work program in the Tonja Village Environment with socialization methods and distributed brochures on tips on choosing or voting properly and correctly. With this activity, it makes people have no fear of coming to the polling station and exercising their voting rights in the 2024 election